Predictors of Mindfulness Meditation and Exercise Practice, from MEPARI-2, a randomized controlled trial - Barrett, Bruce (Mindfulness (N Y), 2019)
OBJECTIVES: Health-supporting behaviors can be challenging to initiate and maintain. Data from the MEPARI-2 randomized trial were used to assess predictors of sustained exercise and meditation practice. METHODS: Adults aged 30 to 69 years not exercising regularly and without prior meditation training were randomized to 8-week trainings in mindfulness meditation, moderate intensity exercise, or observational control, and monitored for 8 months. Exercise participants reported day-to-day minutes of moderate and vigorous activity; mindfulness meditation participants reported minutes of informal and formal practice. Demographic characteristics and psychosocial factors were assessed as predictors of practice. Growth mixture modeling was used to identify higher and lower practice subgroups. RESULTS: 413 participants (75.8% female; mean (SD) age 49.7 (11.6) years) were randomized to exercise (137), mindfulness meditation (138), or control (138), with 390 (95%) completing the study. Seventy-nine percent of exercisers and 62% of meditators reported ≥150 minutes/week practice for at least half of the 37 weeks monitored. Self-reported minutes of mindfulness meditation and/or exercise practice were significantly (p<0.01) predicted by baseline levels of: general mental health, self-efficacy, perceived stress, depressive symptoms, openness, neuroticism, physical activity, smoking status, and number of social contacts. Growth mixture modeling identified subsets of people with moderate (100–200 min/week) and high (300–450 min/week) levels of self-reported practice for both mindfulness meditation (62% moderate; 38% high) and exercise (71% moderate; 29% high). CONCLUSIONS: In this sample, participants randomized to behavioral trainings reported high levels of practice sustained over 37 weeks. Baseline psychosocial measures predicted practice levels in expected directions.